a) 33-14-26-(-7)=[33-(-7)]-14-26=40-14-26=0
b) (-5)-25-(-34)-4=[(-5)-25]-(-34)-4=(-30)-(-34)-4=4-4=0
c) (-6)+5+(-4)+25=[(-6)+(-4)]+5+25=(-10)+5+25=(-5)+25=20
d) 33+34+35+36-13-14-15-16=(33-13)+(34-14)+(35-15)+(36-16)=20+20+20+20=80
CHÚC BẠN HỌC TỐT~💯
a) 33-14-26-(-7)=[33-(-7)]-14-26=40-14-26=0
b) (-5)-25-(-34)-4=[(-5)-25]-(-34)-4=(-30)-(-34)-4=4-4=0
c) (-6)+5+(-4)+25=[(-6)+(-4)]+5+25=(-10)+5+25=(-5)+25=20
d) 33+34+35+36-13-14-15-16
=(33-13)+(34-14)+(35-15)+(36-16)
=20+20+20+20
=80
nhầm nữa đây mới đúng
xin lỗi rất nhiều